The Potential of Art Development in the Present Era: A Case Study of the 'Nggusu Waru' Leadership Philosophy - Abdul Haris Rustaman; Damar Rangga Putra (Budapest International Research and Critics University, 2022)
This investigation was motivated by the Eight Characteristics of Leadership in the Bima community called Nggusu Waru which means octagon, this can be seen in the shape of the Crown of the Bima Kingdom and lare-lare or the entrance gate to the Asi Mbojo Museum. This what inspired me, the Nggusu Waru form found in the Royal Crown shows 8 points of good leadership philosophy. On the one side, many Bimanesse people do not know about the Eight Characteristics of Nggusu Waru's leadership. A Bimanesse humanist and author of the book